Total Kinetic Energy of Fission Fragments based on Fission Product Data - rizal kurniadi (Institut Teknologi Bandung, 2023)
Total kinetic energy (TKE) is the physical quantity that must be acquired during a nuclear fission reaction. This energy is used for various purposes, primarily to determine the spectrum of the second proton. This spectrum is advantageous in the design of nuclear reactors. Various techniques for calculating TKE, from microscopic to macroscopic, have been carried out, from statistical to quantum reviews. This whole technique is solely for obtaining TKE accurately. This paper will review the TKE calculation based on the fission products' experimental results. This fission product data can be in the form of raw experimental data or evaluated data. The calculations are carried out within a macroscopic and statistical review framework. The macroscopic view is a liquid drop model, while the statistics use the random number technique. Because the liquid drop model and the random number technique are very standard, this paper does not review them.